2017
DOI: 10.18632/oncotarget.21324
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal calpain inhibition elicits cerebellar cell death and motor dysfunction

Abstract: Calpain-1 deletion elicits neurodevelopmental disorders, such as ataxia. However, the function of calpain in postnatal neurodevelopment and its mechanisms remain unknown. In this study, we revealed that postnatal intraperitoneal injection of various calpain inhibitors attenuated cerebellar cytosolic calpain activity. Moreover, postnatal application of calpeptin (2 mg/kg) apparently reduced spectrin breakdown, promoted suprachiasmatic nucleus circadian oscillatory protein (SCOP) accumulation in cerebellar tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Apoptosis is not just a simple phenomenon of cell disintegration, but is also closely associated with the onset of a variety of diseases ( 32 ). Apoptosis is one of the main outcomes induced by different treatments on tumor cells ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is not just a simple phenomenon of cell disintegration, but is also closely associated with the onset of a variety of diseases ( 32 ). Apoptosis is one of the main outcomes induced by different treatments on tumor cells ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 is a key apoptotic protease in mammals, and serves a central role in the apoptotic cascade reaction pathway (28). Caspase-3 is activated when cells encounter apoptotic stimulants, which then activate other proteins in the apoptotic pathway to induce apoptosis (29).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is widespread in pancreatic acinar cells and extrapancreatic organs during the development of AP and is closely related to the degree of organ damage. [17][18][19] Valentin et al 20 verified that PLA2 receptor in snake venom or mammalian animals had high affinity, which suggested that the structure of PLA2 in snake venom is similar to that in humans and other mammals, and that snake-derived PLI may inhibit PLA2 in humans. As described previously, PLA2 levels in LPC-treated pancreatic acinar cells was remarkably promoted.…”
Section: Discussionmentioning
confidence: 99%